(untitled) (Journal of the Bangladesh Agricultural University, 2019)
The potato crop is sensitive to environmental factors as optimum planting time of potato depends on the most favorable temperatures extending over the longest period of the crop season and requires less than maximum and above the minimum temperatures for emergence after planting. To secure good yield, the potato crop should be planted in such a time that all the three growth and development phases pass through favorable environmental conditions. Cognizant the above facts, a field experiment was conducted at RDRS Farm, Rangpur during 2014 and 2015 for cultivating potato in different dates with two popular potato varieties like Diamont and Cardinal to find out the optimum planting time of potato production in Bangladesh under short duration rice-based cropping system as well as assess the economic viability of potato cultivation in November. The cost-benefit analysis indicates that no major variation was observed in the performance of two varieties e.g. Diamont and Cardinal. But significant variation was observed in different planting dates. The 22nd November planting of both Diamont and Cardinal produced highest yield (29.2 and 28.8 t/ha1 respectively) compared to other three planting dates like 7th November (27.8 t/ha and 26.9 t/ha), 7th December (21.1 t/ha and 19.8 t/ha) and 22nd December (15.2 t/ha and 14.7 t/ha). The 7th November planting was found economically profitable for both the varieties, where the highest economic return was recorded as TK. 2,06,372/ha for Diamont and TK. 2,08,772/ha for Cardinal. Thus, from the economic point of view, the 7th November planting performed best for both varieties. The cost of production was gradually higher in case of late planting due to use of higher amount of pesticides in the crop field. It may be concluded that potato could be cultivated during 1st half of November month, just after harvesting of short duration aman rice in October that will bring harvesting of potato in 1st half of February which can ensure highest net income from potato cultivation and enables farmers to cultivate next crop like mungbean as additional income. J. Bangladesh Agril. Univ. 17(2): 172–178, June 2019